Integration of ZnO and CuO nanowires into a thermoelectric module - Zappa, Dario; Dalola, Simone; Faglia, Guido; Comini, Elisabetta; Ferroni, Matteo; Soldano, Caterina; Ferrari, Vittorio; Sberveglieri, Giorgio (Beilstein Journal of Nanotechnology, 2014)
Zinc oxide (ZnO, n-type) and copper oxide (CuO, p-type) nanowires have been synthesized and preliminarily investigated as innovative materials for the fabrication of a proof-of-concept thermoelectric device. The Seebeck coefficients, electrical conductivity and thermoelectric power factors (TPF) of both semiconductor materials have been determined independently using a custom experimental set-up, leading to results in agreement with available literature with potential improvement. Combining bundles of ZnO and CuO nanowires in a series of five thermocouples on alumina leads to a macroscopic prototype of a planar thermoelectric generator (TEG) unit. This demonstrates the possibility of further integration of metal oxide nanostructures into efficient thermoelectric devices.
Keywords: copper oxide; nanowires; thermoelectric; zinc oxide